DERMOCOSMETICS: ORIGIN, EVOLUTION AND TECHNOLOGICAL TRENDS - Ferreira Nogueira, Juscelia (Health and Society, 2023)
The objective of this research was to raise a discussion about Dermocosmetics and the technological trends applied in cosmetics and dermocosmetics, and which is the importance of the pharmaceutical professional in this health/beauty segment. Dermocosmetics are products that bring in their composition pharmacological active compounds with therapeutic activity, which are similar to dermatological medicines for topical use. That is, they are products that go beyond the epidermis, with actives that reach the deepest layers of the skin and that bring better results, acting from the inside out. While dermocosmetics general physiological changes, causing changes in the skin, traditional cosmetics work with instant action. They improve the momentary appearance, but do not act on the real causes of these problems. The methodology used in this research was the descriptive qualitative literature review, with bibliographic bases obtained through theses, monographs, scientific technical articles, books, periodicals and virtual library. The period of publications collected for the research was from 2010 to 2021, in Portuguese and English.